2020
DOI: 10.1074/jbc.ra120.013618
|View full text |Cite
|
Sign up to set email alerts
|

Differences in self-association between kindlin-2 and kindlin-3 are associated with differential integrin binding

Abstract: The integrin family of transmembrane adhesion receptors coordinate complex signaling networks that control the ability of cells to sense and communicate with the extracellular environment. Kindlin proteins are a central cytoplasmic component of these networks, directly binding integrin cytoplasmic domains and mediating interactions with cytoskeletal and signaling proteins. The physiological importance of kindlins is well established, but how the scaffolding functions of kindlins are regulated at the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“… 102 The authors also provided evidence to show that disruption of the trimer interface promotes integrin‐mediated cell adhesion and spreading 102 . Moreover, Kadry et al in a recent study suggested that both kindlin‐2 and kindlin‐3 can self‐associate into 2–4 molecule oligomers via their F2PH domains but with an interface different from that in the truncated kindlin‐2 dimer 103 . The F3 domain is clearly not involved since deletion of F3 domain increased the self‐association of kindlin molecules 103 .…”
Section: Kindlins and Kindlin Networkmentioning
confidence: 99%
See 1 more Smart Citation
“… 102 The authors also provided evidence to show that disruption of the trimer interface promotes integrin‐mediated cell adhesion and spreading 102 . Moreover, Kadry et al in a recent study suggested that both kindlin‐2 and kindlin‐3 can self‐associate into 2–4 molecule oligomers via their F2PH domains but with an interface different from that in the truncated kindlin‐2 dimer 103 . The F3 domain is clearly not involved since deletion of F3 domain increased the self‐association of kindlin molecules 103 .…”
Section: Kindlins and Kindlin Networkmentioning
confidence: 99%
“…Moreover, Kadry et al in a recent study suggested that both kindlin‐2 and kindlin‐3 can self‐associate into 2–4 molecule oligomers via their F2PH domains but with an interface different from that in the truncated kindlin‐2 dimer 103 . The F3 domain is clearly not involved since deletion of F3 domain increased the self‐association of kindlin molecules 103 . Given that the majority of either isolated kindlin‐2 or kindlin‐3 is monomeric as shown in all these studies, careful investigation is needed to examine if or when kindlin oligomerization occurs in physiological context.…”
Section: Kindlins and Kindlin Networkmentioning
confidence: 99%
“…Whether dimerization is a general mechanism of all Kindlin members to cluster integrins remains to be shown. Interestingly, recent crystallization studies suggest the formation of trimeric or even higher Kindlin complexes, which are unable to bind integrins ( 66 , 67 ). Future studies will show whether Kindlin dimer/multimerization does occur and have an impact on integrin activity regulation in vivo and how this is regulated by upstream signals.…”
Section: Introductionmentioning
confidence: 99%
“…All of these crystal structures have verified the central role of the QW motif in the F3 subdomains of the three kindlins in integrin CT binding. Biophysical studies have yielded variable results as to the significance of multimerization in integrin activation [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%